2005
DOI: 10.1103/physrevb.72.075308
|View full text |Cite
|
Sign up to set email alerts
|

Density-dependent spin susceptibility and effective mass in interacting quasi-two-dimensional electron systems

Abstract: Motivated by recent experimental reports, we carry out a Fermi liquid many-body calculation of the interaction induced renormalization of the spin susceptibility and effective mass in realistic two dimensional (2D) electron systems as a function of carrier density using the leading-order 'ladder-bubble' expansion in the dynamically screened Coulomb interaction. Using realistic material parameters for various semiconductor-based 2D systems, we find reasonable quantitative agreement with recent experimental susc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

5
15
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(21 citation statements)
references
References 21 publications
5
15
1
Order By: Relevance
“…1 In particular, s ‫ء‬ and m ‫ء‬ are expected to be larger than the band values ͑ s,b and m b ͒ for large r s . [1][2][3][4][5][6][7] Enhancements of s ‫ء‬ and m ‫ء‬ at large r s are indeed observed in a number of different 2DESs. [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] In addition to r s , the role of spin and valley degrees of freedom on s ‫ء‬ and m ‫ء‬ renormalization has been explored both experimentally 15,20,[22][23][24][25] and theoretically.…”
mentioning
confidence: 68%
See 3 more Smart Citations
“…1 In particular, s ‫ء‬ and m ‫ء‬ are expected to be larger than the band values ͑ s,b and m b ͒ for large r s . [1][2][3][4][5][6][7] Enhancements of s ‫ء‬ and m ‫ء‬ at large r s are indeed observed in a number of different 2DESs. [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] In addition to r s , the role of spin and valley degrees of freedom on s ‫ء‬ and m ‫ء‬ renormalization has been explored both experimentally 15,20,[22][23][24][25] and theoretically.…”
mentioning
confidence: 68%
“…This unexpected result was subsequently explained by theoretical studies. 5,26,27 The valley susceptibility ͑ v ‫ء‬ ϰ E 2 ‫ء‬ m ‫ء‬ ͒ of AlAs 2DESs, defined as the rate of valley polarization with applied strain ͑in analogy to s ‫ء‬ which is defined as the rate of spin polarization with applied magnetic field͒, has also been measured 22 ͑E 2 ‫ء‬ is the conduction-band deformation potential͒. It was found that v ‫ء‬ depends on the spin subband occupation 28 in a similar way that s ‫ء‬ depends on the valley occupation.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…1 (c) shows the extracted m * for the three different samples. We obtain a density-averaged mass of m * ≈ 0.62 m e which does not show any obvious dependence neither on n nor on B [17,18].…”
mentioning
confidence: 72%